2003
DOI: 10.1016/s0003-2670(03)00760-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the recognition ability of molecularly imprinted materials by surface plasmon resonance (SPR) spectroscopy

Abstract: Polysulfone with an oligopeptide derivative of glutamyl residues (PSf-E 5.8 ) was evaluated as a candidate material for molecular recognition. PSf-E 5.8 was prepared from the N-carboxyanhydride of ␥-benzyl-l-glutamate (Glu(OBzl)-NCA) initiated by aminomethylated polysulfone (PSf). Films with molecular recognition sites with preference to adenosine (As) were prepared from PSf-E 5.8 by an alternative molecular imprinting method using 9-ethyladenine (9-EA) as a print molecule. The molecular recognition phenomena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 34 publications
2
23
1
Order By: Relevance
“…In the previous study [27,31], the affinity constant was observed to increase with the decrease in molecular imprinting ratio; in other words, at the lower molecular imprinting ratio, more functional groups in the candidate polymer interacted with one print molecule, resulting in a higher affinity constant. Similar phenomena were also observed in the present study, and the affinity constants for the molecularly imprinted nanofiber membranes gave higher values than those of the usual molecularly imprinted membranes.…”
Section: Adsorption Isothermsmentioning
confidence: 83%
“…In the previous study [27,31], the affinity constant was observed to increase with the decrease in molecular imprinting ratio; in other words, at the lower molecular imprinting ratio, more functional groups in the candidate polymer interacted with one print molecule, resulting in a higher affinity constant. Similar phenomena were also observed in the present study, and the affinity constants for the molecularly imprinted nanofiber membranes gave higher values than those of the usual molecularly imprinted membranes.…”
Section: Adsorption Isothermsmentioning
confidence: 83%
“…On the bisphenol segment, H 3,5 and H 2,6 remain largely unchanged. Benzyl protons H [15][16][17] are all within 0.2 ppm of one another, the furthest downfield being H 15 , which is affected by the electronic effect of the imine group. The H 17 1 H triplet is coupled with H 16 .…”
Section: Nmr Of Psf-benziminesmentioning
confidence: 97%
“…The molecular recognition of the prepared films toward the target molecule adenosine (As) was evaluated by surface plasmon resonance (SPR) spectroscopy. 17 During the measurement, a 0.02 wt % NaN 3 aqueous buffer was passed over the molecularly imprinted material surface at 5 mm 3 min…”
Section: Assessment Of Potential Sensor Devices Derived From Benzylammentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular Figure 7 Affinity constants between As and molecular recognition sites converted from various candidate materials. recognition sites toward As have been previously constructed from H-Asp(OcHex)-Ile-Asp(OcHex)-Glu(OBzl)-O-CH 2 -tetrapeptide derivative (DIDE), 30 polysulfone with oligopeptide derivative of glutamyl residues (PSf-E 5.8 ), 31 cellulose acetate (CA) with 40% acetyl content, 30 carboxylated polysulfone (PSf-COOH) with the degree of substitution of 0.88, 30 Torlon (polyamide-imide), 32 hydrophilic water-soluble proteins, 19 and membrane proteins 33 from Geobacillus thermodenitrificans DSM465. The affinity constants between As and the molecular recognition sites converted from those candidate materials are summarized in Figure 7 together with the chemical structures of those materials for convenience.…”
Section: Adsorption Isotherms Of As and Gs On The 9-ea Imprinted Filmmentioning
confidence: 99%